Nursing of a patient with hemorrhagic transformation after mechanical thrombectomy for progressive ischemic stroke (1例进展性缺血性脑卒中机械取栓术后出血转化患者的护理) - ZHANG Xiuping (张秀萍); WEI Xiaojie (魏晓洁); YANG Xiaoli (杨晓丽); LIU Xiangcai (刘相彩) (中西医结合护理)
To summarize the nursing experience of a patient with hemorrhagic transformation after mechanical thrombectomy for progressive ischemic stroke. The key points of nursing included: taking emergency rescue with integrated medical care and making full use of the “Golden Time” for life-saving; Multidisciplinary team collaboration to dynamically adjust diagnosis and treatment strategies; Multi-directional precision care for quantitative visual management; dynamic assessment of disease changes and active prevention and treatment of complications. After 41 days of active treatment and refined care by a multidisciplinary team, the patient was discharged in stable condition uneventfully. A multidisciplinary team is required to carry out dynamic evaluation, individualized intervention and whole process management of the patient with hemorrhagic transformation after intervention therapy for stroke, in order to reduce the risk of mortality and disability, and improve the prognosis of the disease. (本文总结1例进展性缺血性脑卒中机械取栓术后出血转化患者的护理经验。医护一体化紧急救护, 抓住急救“黄金时间”; 多学科诊疗团队协作, 动态调整诊疗策略; 多方位精准护理, 实现量化可视化管理; 动态评估病情变化, 积极预防与处理并发症。经过41 d的多学科团队的积极治疗与精细化护理, 患者病情稳定顺利出院。针对脑卒中介入治疗后出血转化患者, 需建立多学科协作机制, 通过动态评估、个性化干预及全程化管理, 有效降低致死致残风险, 改善预后。)